Control of Heterogeneous Fe(III) (Hydr)oxide Nucleation and Growth by Interfacial Energies and Local Saturations - Yandi Hu; Neil, Chelsea; Lee, Byeongdu; Jun, Young-Shin* (Environmental Science & Technology, 2013)
To predict the fate of aqueous pollutants, a better understanding of heterogeneous Fe(III) (hydr)oxide nucleation and growth on abundant mineral surfaces is needed. In this study, we measured in situ heterogeneous Fe(III) (hydr)oxide nucleation and growth on quartz, muscovite, and corundum (Al2O3) in 10–4 M Fe(III) solution (in 10 mM NaNO3 at pH = 3.7 ± 0.2) using grazing incidence small-angle X-ray scattering (GISAXS). Interestingly, both the fastest heterogeneous nucleation and slowest growth occurred on corundum. To elucidate the mechanisms, zeta potential and water contact angle measurements were conducted. Electrostatic forces between the charged Fe(III) (hydr)oxide polymeric embryos and substrate surfaces—which affect local saturations near the substrate surfaces—controlled heterogeneous growth rates. Water contact angles (7.5° ± 0.7, 22.8° ± 1.7, and 44.8° ± 3.7 for quartz, muscovite, and corundum, respectively) indicate that corundum has the highest substrate–water interfacial energy. Furthermore, a comparison of structural mismatches between the substrates and precipitates indicates a lowest precipitate–substrate interfacial energy for corundum. The fastest nucleation on corundum suggests that interfacial energies in the solution–substrate–precipitate system controlled heterogeneous nucleation rates. The unique information provided here bolsters our understanding of nanoparticle–mineral surface interactions, mineral surface modification by iron oxide coating, and pollutant transport.